Gain-of-Function STIM1 L96V Mutation Causes Myogenesis Alteration in Muscle Cells From a Patient Affected by Tubular Aggregate Myopathy - Conte, Elena; Pannunzio, Alessandra; Imbrici, Paola; Camerino, Giulia Maria; Maggi, Lorenzo; Mora, Marina; Gibertini, Sara; Cappellari, Ornella; De Luca, Annamaria; Coluccia, Mauro; Liantonio, Antonella (Frontiers in Cell and Developmental Biology, 2021)
Tubular Aggregate Myopathy (TAM) is a hereditary ultra-rare muscle disorder characterized by muscle weakness and cramps or myasthenic features. Biopsies from TAM patients show the presence of tubular aggregates originated from sarcoplasmic reticulum due to altered Ca2+ homeostasis. TAM is caused by gain-of-function mutations in STIM1 or ORAI1, proteins responsible for Store-Operated-Calcium-Entry (SOCE), a pivotal mechanism in Ca2+ signaling. So far there is no cure for TAM and the mechanisms through which STIM1 or ORAI1 gene mutation lead to muscle dysfunction remain to be clarified. It has been established that post-natal myogenesis critically relies on Ca2+ influx through SOCE. To explore how Ca2+ homeostasis dysregulation associated with TAM impacts on muscle differentiation cascade, we here performed a functional characterization of myoblasts and myotubes deriving from patients carrying STIM1 L96V mutation by using fura-2 cytofluorimetry, high content imaging and real-time PCR. We demonstrated a higher resting Ca2+ concentration and an increased SOCE in STIM1 mutant compared with control, together with a compensatory down-regulation of genes involved in Ca2+ handling (RyR1, Atp2a1, Trpc1). Differentiating STIM1 L96V myoblasts persisted in a mononuclear state and the fewer multinucleated myotubes had distinct morphology and geometry of mitochondrial network compared to controls, indicating a defect in the late differentiation phase. The alteration in myogenic pathway was confirmed by gene expression analysis regarding early (Myf5, Mef2D) and late (DMD, Tnnt3) differentiation markers together with mitochondrial markers (IDH3A, OGDH). We provided evidences of mechanisms responsible for a defective myogenesis associated to TAM mutant and validated a reliable cellular model usefull for TAM preclinical studies.